2016
DOI: 10.1016/j.fertnstert.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Locostatin, a disrupter of Raf kinase inhibitor protein, inhibits extracellular matrix production, proliferation, and migration in human uterine leiomyoma and myometrial cells

Abstract: Our results indicate that RKIP may be involved in leiomyoma pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…3B), suggesting that ILK in decidualized ESCs transmit signals through the GSK3b, but not the Akt, pathway. Because a recent study also found that reduced GSK3b expression led to the reduction of proliferation of uterine myometrial cells (35), the significantly decreased numbers of the decidualized ESCs with effective ILK knockdown in the present study ( Fig. 3G) suggest that ILK may play a role in cellular proliferation by acting through the GSK3b signaling pathway.…”
Section: Discussionsupporting
confidence: 62%
“…3B), suggesting that ILK in decidualized ESCs transmit signals through the GSK3b, but not the Akt, pathway. Because a recent study also found that reduced GSK3b expression led to the reduction of proliferation of uterine myometrial cells (35), the significantly decreased numbers of the decidualized ESCs with effective ILK knockdown in the present study ( Fig. 3G) suggest that ILK may play a role in cellular proliferation by acting through the GSK3b signaling pathway.…”
Section: Discussionsupporting
confidence: 62%
“…The cell sheet migration inhibitor, Locostatin is the only available potent RKIP inhibitor identified till date (Shemon et al, 2009;Rudnitskaya et al, 2012). Locostatin functions as a PPI inhibitor by binding RKIP and abrogates it from interacting with C-Raf (Beshir et al, 2011;Janjusevic et al, 2016). In spite of the accessibility of Locostatin, design of better probes to hinder the association of RKIP with C-Raf for future implications is needed on an urgent basis.…”
Section: Discussionmentioning
confidence: 99%
“…(2011) 29 evidenced in 235 women with a diagnosis of uterine fibroids in early pregnancy that breastfeeding was not related to fibroid regression three-six months post-delivery. These conflicting results can be explained by the different dimensions of included fibroids, with probably a less evident effect of breastfeeding in case of large fibroids, and by the heterogeneous sensitivity of uterine fibroids to different mediators, not only represented by ovarian steroids, but also by other hormones 30 , mediators 31 , and growth factors 32 . In particular, Busnelli et al .…”
Section: Discussionmentioning
confidence: 99%
“…indicate that oxytocin stimulates the proliferation of both myometrial and leiomyoma cells and could, therefore, counteract the effect of the hypoestrogenic state during breastfeeding on fibroid regression 29 . Mediators like Raf kinase inhibitor protein (RKIP) and growth factors activating multiple signaling pathways like Smad 2/3, ERK 1/2, PI3K, or β-catenin may contribute to regulate major cellular processes, including inflammation, proliferation, angiogenesis, and fibrosis which are linked to fibroids development and growth, both during pregnancy and in non-pregnant state 31,32 . It is possible to speculate that also the cellularity of fibroids 33 may explain those different trends: the cellular component can grow or shrink in response to different hormonal levels, and the fibrous component could be more stable or be influenced by other non-hormonal mediators; however, further evidence is still needed in this regard.…”
Section: Discussionmentioning
confidence: 99%